Translation Procedure of Full Moon in the Midwest, Is it the Sound of Pines, and the Moon Poems by John H. McGlynn - Ina Astarina (Journal of English Language Teaching and Cultural Studies, 2019)
This research aims to describe the use of translation procedures in translating Full Moon in the Midwest, Is it the Sound of Pines, and The Moon poems. This research was conducted using a qualitative approach. This was done that researchers can describe the use of translation strategies applied by translators. Data sources are three poems by Taufik Ismail entitled Pantun Terang Bulan di Midwest, Adakah Suara Cemara and Bulan, and translated into English by McGlynn with the title Full Moon in the Midwest, Is it the Sound of Pines and The Moon. In analyzing the data, all translated poems and original poems were analyzed, and the results of the analysis were compared to see in what aspects each of the poems of the translation and poem was equivalent and faithful. The result shows that in terms of meaning, aesthetic values, and structure, Full Moon in the Midwest, Is it the Sound of Pines and The Moon is the result of a faithful translation from Pantun Terang Bulan di Midwest, Adakah Suara Cemara, and Bulan. Each target language successfully defends the meaning of the source language. In other words, the translation of the three poems can meet fidelity.